J-shaped association between metabolic score for visceral fat and albuminuria risk: a population-based study - Zhang, Yuren; Xu, Jinting; Zhang, Yiping; Chen, Yinan; Liu, Qiaolan (Frontiers in Endocrinology, 2025)
ObjectiveMetabolic Score for Visceral Fat (METS-VF) represents a novel metric for assessing visceral fat and its associated cardiometabolic risks. This study evaluated the relationship between METS-VF and the prevalence of albuminuria among U.S. adults.MethodsA cross-sectional study enrolled participants aged 20 years and older from the National Health and Nutrition Examination Surveys (NHANES) between 1999 and 2018. Albuminuria was identified as a urinary albumin-to-creatinine ratio (UACR) of 30 mg/g or higher. The Metabolic Score for Visceral Fat (METS-VF) was assessed using the Metabolic Score for Insulin Resistance (METS-IR), waist-to-height ratio (WHtR), age, and sex. The association between METS-VF and the risk of albuminuria was explored.ResultsAmong the 22514 adult participants, the albuminuria group exhibited higher METS-VF levels compared to the non-albuminuria group. Furthermore, the prevalence of albuminuria increased progressively with rising METS-VF levels. Adjusted multivariable logistic regression analysis revealed a significant association between METS-VF and the risk of albuminuria (OR = 1.406, 95%CI:1.243-1.590, P<0.001). Restricted cubic spline analysis demonstrated a J-shaped dose-response relationship, with a threshold value of 6.128. Mediation analysis further identified hemoglobin A1c (HbA1c), blood pressure, oxidative stress, and inflammation as partial mediators of this association.ConclusionMETS-VF may act as a useful epidemiological indicator for assessing visceral fat’s role in albuminuria risk among U.S. adults. Additional large-scale prospective research is necessary for confirmation.